ОБ УВЕЛИЧЕНИИ КОЛИЧЕСТВА ЗАИМСТВОВАНИЙ В СОВРЕМЕННОМ КАРАКАЛПАКСКОМ ЯЗЫКЕ - Кощанов, К.М.; Кощанов, Ш.Ж. (SCIENCE and SOCIETY, 2021)
The article deals with enriching the Karakalhak language with foreign borrowings
Keywords: borrowing; assimilation; terms; lexics; subjects; concept